Nurturing Care: A Holistic Approach to Early Childhood Development - Serap Deniz (Çocuk Dergisi)
Early childhood (ECC) is the main period of cognitive development, physical and mental health in children. The well-being of future generations depends on early childhood development and care. Poverty, malnutrition, violence, gender inequality, environmental pollution and caregiver mental health problems threaten the development of young children and prevent them from being physically and mentally healthy, being happy, having positive relationships and being productive adults. Nurturing Care (NC) is a policy framework proposed by the World Health Organization (WHO), UNICEF and other stakeholders, aimed at achieving national and global goals to help children survive and thrive, in order to transform health and human potential. Its components are health, adequate nutrition, responsive care, early learning opportunities and safety. NC aims to provide family-centered, holistic services to each child, especially in the first three years of life, starting from pregnancy. The aim of this review is to increase the awareness of NC in Turkey and to share studies from other countries.